The Local Wisdom of Patorani Fishermen A Sustainable Solution to Poverty and the Sustainable Development Goals (SDGs) - Erman Syarif; Abdul Malik; Marlina (PT ARRUS Intelektual Indonesia, 2025)
The local wisdom of Patorani fishermen plays an important role in preserving the marine ecosystem and supporting community welfare. Their ecological ethics, such as prohibiting fishing during certain periods, using environmentally friendly fishing gear, and collective practices in boat maintenance and distribution of catches, reflect sustainable fisheries management. These traditions not only preserve coastal ecosystems but also strengthen socio-economic resilience through solidarity, cooperation, and fair economic practices. This value system contributes to poverty reduction, decent work, and marine conservation in line with Sustainable Development Goals (SDGs) 1, SDG 8, and SDG 14. However, limited access to markets, technology, and capital remains a challenge in improving livelihoods. Strategic efforts are needed to preserve and revive Patorani wisdom amid modernization, including digital cultural documentation, integration into coastal education, and the development of creative economic initiatives. Collaboration between the government, academics, and fishing communities is essential to increase empowerment and support sustainable development.